Inuit Harvesting Strategies in the Canadian Arctic and Implications for Wildlife Management - Netherwood, Marshall (Scott Polar Research Institute, 1987)
The file processed with OCR is smaller and allows copying and pasting (though this may contain errors). The file without OCR is much larger and does not allow copying and pasting but the visual quality is generally superior. The thesis analyses two topics: native harvesting strategies and selected cases of over-exploitation. Its purpose is to assess the credibility of the assumption that hunter-gatherer societies do not have a system of self-regulation. Theoretical explanations and models are described to elicit underlying principles and coherent systems in hunter-gatherer harvesting strategies and adaptation processes. Two annual cycles of the Netsilik Inuit are discussed and examined in a formal theory model to analyse what changes and effects occurred when the rifle was introduced to their subsistence economy. The evidence supporting the Pleistocene overkill theory and the claim that hunters over-exploited some of the major barren-ground caribou herds in the Northwest Territories is examined. The evidence is found to be unproven and inconclusive. The nature of self-regulation in hunter-gatherer societies as supported by ethnographic literature is described and determined to be extant. Hunters practice control in harvesting through the acquired knowledge and institutional means to monitor and avert overhunting. It is also evident that harvesters have a sound basis of knowledge and expertise in animal ecology. In the appendix. four cases are described where the traditional system of harvesting/management has proven successful and superior to state imposed wildlife management. The thesis concludes that the assumption is erroneous: there exists a socially-constructed system of self-regulation. The implications for wildlife management are discussed and it is concluded that although there is greater recognition of the native system of harvesting/management today, it is not generally accepted that they possess the knowledge and expertise to organize an effective management strategy.